The Effect Of Digital Transformation And Lifestyle On Saving Decisions Mediated By User Satisfaction Of Kb Star In Jember Regency - Devy Kristiningrum; Deasy Wulandari; Elok Sri Utami (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the influence of digital transformation and lifestyle on saving decisions, with user satisfaction as a mediating variable among users of the KB Star application in Jember Regency. Digital transformation enables financial institutions to offer efficient, fast, and integrated services, while lifestyle reflects customer preferences and behaviors that also shape financial decisions. KB Star, as a digital banking platform by KB Bank, has experienced a significant increase in users; however, not all customers utilize its features to the fullest. This research adopts a quantitative approach using explanatory research methods. Data were collected through questionnaires distributed to 200 respondents who were active users of KB Star. The results indicate that digital transformation and lifestyle significantly influence user satisfaction, and that satisfaction acts as a mediating factor in influencing savings decisions. This study provides implications for the development of digital services oriented toward customer satisfaction and lifestyle needs as a strategy to enhance loyalty and financial decision-making in the digital era.